(untitled) (Bioscience Journal, 2020)
This research study aimed at evaluating the content related to pediatric dentistry addressed in civil service examinations in the state of Paraíba through the analysis and classification of questions. Questions related to pediatric dentistry addressed in civil service examinations for the dentist position in the Family Health Program, held in the state of Paraíba, between the years 2001 and 2017 were evaluated. Across the state, 107 civil service examinations were identified and, when applying the exclusion criteria, 9 identical tests were found, consequently, being removed, totaling 98 examinations. After the analysis, 3,949 questions were obtained and only 54 questions were related to pediatric dentistry, representing 1.36% of total questions. The questions were classified according to the topic and the cognitive level according to the BLOOM’s revised taxonomy. Results showed that topics related to oral rehabilitation and surgical management, including questions regarding anesthesia, surgery, pulp therapy, endodontic treatment, operative and restorative dentistry, dental materials, traumatic injuries and prosthesis/rehabilitation corresponded to 42% of the questions. The most prevalent cognitive domains were recall and analyze, corresponding to 45% and 29%, respectively. Thus, questions concerning oral rehabilitation and surgical management were the most addressed in civil service examinations, in which the domains remember and analyze were predominant. There were no questions requiring complex cognitive domain such as assessing and creating.